Changes in Blood Glucose and Cortisol in Nile Tilapia (Oreochromis niloticus) with Different Salinities - Satiti, Cinca Hayyu Putri; Faqih, Abdul Rahem; Mahmudi, Mohammad; Moehammad, Khibar Syiar (The Journal of Experimental Life Science, 2025)
Nile tilapia (Oreochromis niloticus) is a freshwater fish of high economic value that can tolerate a wide range of salinities, offering potential for the utilization of idle coastal ponds in northern Java. This study aimed to evaluate the physiological stress responses of Nile tilapia exposed to different salinity levels by measuring blood glucose levels, cortisol concentrations, and survival rates. The experiment was conducted for 28 days at the Sumberpasir Freshwater Fisheries Laboratory, Malang, using a Completely Randomized Design with four salinity treatments (0, 7, 14, and 21 ppt) in triplicate. Data on blood glucose and cortisol were analyzed using ANOVA (p < 0.05), while survival rate and water quality were analyzed descriptively. The results showed that salinity significantly affected blood glucose levels, with the highest value recorded at 21 ppt (115±39.2 mg.dL-1) and the lowest at 0 ppt (63±29.9 mg.dL-1). In contrast, cortisol levels were not significantly different among treatments, with the lowest average at 14 ppt (33.23±4.17 ng.mL-1). The highest survival rate was found at 0 and 7 ppt (100%), declining to 98% and 93% at 14 and 21 ppt, respectively. It is concluded that Nile tilapia can adapt physiologically to salinity levels of up to 21 ppt, with 14 ppt being the most stable level for stress adaptation. Further study is recommended to assess long-term growth and molecular indicators supporting the development of brackish water aquaculture.